Enhancing cadastral surveys by facilitating the participation of owners. Issue 344 (September 2015) - Mourafetis, G.; Apostolopoulos, K.; Potsiou, C.; Ioannidis, C.
Abstract : While some countries have over centuries developed a nation-wide spatial framework, some others have been left behind. However, because of the global economic and social challenges, there is an urgent need for those countries to develop similar systems in a fast and efficient way for their economic survival. Building such a framework should be always based on each country's resources and capacities. In systematic cadastral registrations, the participation of owners has always been crucial for the success of the project. Within this concept, the authors investigate the potential of new tools to increase the participation of land right holders and local volunteers (non-professionals) and to enhance the cadastral surveying procedure. A hybrid "crowdsourcing" approach is proposed, mainly based on the direct participation of property rights holders in which the role of the cadastral surveyor is crucial. A commercial application for smartphones is tested. The smartphone's GPS is used only for the general positioning on the basemap to avoid gross errors when owners are not accustomed in using aerial photos. A recent orthoimage of 20 cm pixel size in urban areas and an orthoimage basemap of 50 cm pixel size in rural areas is used as the basemap. Once roughly positioned, owners may then digitise the boundary coordinates on the basemap off-line, with little training support; they may also work from a distance. In areas where the property boundaries are easily recognised on the basemap, boundary coordinates have the expected geometric accuracy that can be achieved on the basemap while no gross errors are detected. Attachment of photos is also possible (e.g. photos of the property or of the deeds). Restricted access to personal data may also be achieved. The method is also useful for cadastre updating purposes (e.g. the periodic updating of buildings database).